Perspective Cognitive Warm-up Voice (Al-Academy, 2018)
The aim of this research is to find out about the methods used by the teachers of the subjects (choir, voice training, singing groups) used to warm up in voice training. In the Department of Music of the Faculty of Fine Arts University of Baghdad. The limits of this research were for the academic year (2017-2018). Explanation in the theoretical framework of warm-up types The first part of the body warms the body in terms of relaxation, body moderation, head rotation, tongue exercises, mouth opening, facial mask movements, yawning.The second course will warm up the sound exercises warm up the sound through different ladders (diatonic and chromate), and ladder accordions.And the third topic warm up the imprisonment of the soul. Such as prolonged breathing, self-locking, slow breathing, breathing, and self-confidence. By studying the theoretical framework literature, the researcher built her research tool in the form of a questionnaire that she presented to the methodological and specialized experts. And won majority acceptance. The researcher took the interview to collect the answers of the teachers after the collection of the answers. She analyzed and concluded that the warm-up process in the Faculty of Fine Arts was different among the teachers.